Hi-Fi Intercom / Mohd Rizal Ishak and Mohd Isamir Md Isa - Ishak, Mohd Rizal; Md Isa, Mohd Isamir (1999)
These projects are inspiration for communication system. The intercom system can called intercommunication system. This system can be defined as an audio-frequency amplifier system that provides two - way voice communication between two or more locations, which are using high frequency, and in the same structure. Each station contains a dynamic loudspeaker that also serves as microphone. The amplifier can be at a station, or each station may have its own amplifier. Connection between stations can be made buy wire or carrier signals travelling over electric wiring in the building. It also widely used on ships and large aircraft. In other words, an option on many business phone system which allows you to use an abbreviated dialing sequence to react another telephone connected to the same Communications System and it also called “Hi-Fi Intercom”.